Over & above. Trampoline gymnastics towards world class performance - Kelly, J. (Meyer & Meyer, 2014)
When we watch accomplished athletes in any Sport, whether it is track and field, swimming or any of the ball sports, they perform with a style and elegance that belies the complexity of the skills they are employing. This quality of movement is not motivated by the desire to score high execution marks but is a by-product of the balance, timing, power and precise decision-making required by their specific event. It is time that coaches of trampoline gymnastics became more aware that aesthetic excellence is simply the logical outcome of that same balance, timing, power and decision-making. Any coach who can fully appreciate the implications of that paradox will be well on the way to developing World Class Performance. Jack Kelly is one of the most successful coaches in trampoline gymnastics and has, with his innovative thinking, led several athletes to European and World Championships. He has developed World Champions at junior, youth, and senior level. His expertise as an adviser on coach education and gymnast performance is in demand by many countries, the most recent being Canada, the Netherlands, and Singapore. Now in his seventies, his thinking is as current as anyone's within the sport and he continues to adapt and develop in response to world trends within trampoline gymnastics. In this comprehensive book, he outlines a process for developing world class skills in trampoline gymnastics. The methods described here have helped remodel the technique of numerous advanced performers, enabling them to break through to the next level. This is followed by a compendium of theoretical and practical guidance based on Kelly's years of striving for, and achieving, world class results. Along the way, Jack Kelly highlights the significant influences on his life that have made him into the coach he has become. Thus, the reader has the opportunity to benefit from the author's extensive knowledge and experience. One of the main theme of this book is the development of technical excellence. It is important to introduce conditioning at the right time, commensurate with the gymnast's level of commitment to their particular goals within the sport. It must be appreciated that a high percentage of young people is attracted to trampolining simply because it looks like fun. Unlike more high-profile sports, there is an absence of readily available role models through the media so beginners rarely have World Class ambitions from the outset. They (and their parents) may have little idea they are entering a sport that requires the highest levels of physical and technical preparation. The coach needs to exercise sound judgment to make sure the developing gymnast is ready (physically and mentally) to engage with the conditioning program. This is where gymnastics clubs who cater to the full range of disciplines have a significant advantage, because their young members will have grown up with televised role models and a background of conditioning from day one. It is interesting to note that many outstanding trampoline gymnasts have come from a background of artistic gymnastics where it has been discovered that, while having strength and acrobatic ability, they could not tick all the flexibility boxes. This gave rise to Mitch Fenner's comment that "the best trampolinists are failed gymnasts!" - a generalization perhaps but not without an element of truth.